In Search for Yardstick Competition: Property Tax Rates and Electoral Behavior in Italian Cities - Massimo Bordignon; Floriana Cerniglia; Federico Revelli (Center for Economic Studies and ifo Institute (CESifo), 2002)
Do citizens engage in comparative performance evaluation across local governments? And if they do, how can we disentangle this behavior from other forms of strategic interactions among local governments or simple spatial correlation across neighboring jurisdictions? We use spatial econometrics techniques and the institutional characteristics of the Italian system to test if some theoretically derived predictions of yardstick competition theory are supported by data, estimating to this aim both a tax setting and a popularity equation. The results show that local tax rates are positively auto-correlated among neighboring jurisdictions when the mayors run for re-election, while this correlation is absent where either the mayors face a term limit or where they are backed by an overwhelming majority in the local council. Both results are in clear agreement with yardstick theory. On the other hand, the results of the estimation of the popularity equation are less supportive of the theory, possibly as a result of the difficulty in controlling for public service quality and the simultaneous setting of multiple policy instruments.
Keywords: 330; local property tax setting; yardstick competition; spatial auto-correlation.